The effect of aquatic -training on Improving Cardiorespiratory Fitness in Senior Football Players - ouali, abdennour; lamara, salim (sports creativity, 2025)
The study aimed to investigate the impact of aquatic exercises on improving cardiorespiratory fitness among senior football players. The research was conducted on a purposive sample consisting of 10 players from the WRB M’sila football team. Where they were divided into two equal experimental groups. The first experimental group underwent an aquatic exercise program, while the second group underwent the team’s regular training program; The researcher used the experimental method by conducting pre- and post- measurements of cardiorespiratory fitness using the Ruffier-Dickson test, The researcher also made use of a program of SPSS. The results revealed a significant improvement in the cardiorespiratory fitness of the experimental group compared to the control group. Based on the findings, the researcher emphasized the importance of utilizing aquatic exercises to enhance cardiorespiratory efficiency and provided several related recommendations.